Diseminasi Informasi mengenai Penyakit Parkinson pada Pasien Rawat Jalan Poliklinik Neurologi Rumah Sakit Universitas Mataram - Herpan Syafii Harahap; Ilsa Hunaifi; Muhammad Ghalvan Sahidu; Yanna Indrayana; Safat Wahyudi; Baiq Hilya Kholida; Stephanie Elizabeth Gunawan (Universitas Mataram, 2023)
Parkinson's disease is a neurodegenerative disease that is quite common in the elderly population, which is the second most common after Alzheimer's disease. Patients with advanced Parkinson's disease will rely heavily on family members to carry out their basic daily activities. This activity aims to disseminate information related to Parkinson's disease to visitors to the Neurology Polyclinic at the University of Mataram Hospital. The activities carried out included pre-tests, topic presentations, and post-tests. The enthusiasm of the participants in this activity was recorded as a photo documentation. Statistical analysis using paired t-test was carried out to test whether there was a significant difference between the mean pre-test and post-test scores of the participants. A total of 15 participants participated in this whole series of activities with great enthusiasm. There was a significant increase in the post-test mean value compared to the pre-test mean value (p = 0.002). Community service activities in the form of counseling are effective in increasing participants' knowledge about Parkinson's disease.